2019
DOI: 10.1111/jphp.13195
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of particle behaviour in a realistic human airway model with varying inhalation patterns

Abstract: Objectives For dry powder inhalers, the airflow properties in the airways could affect the deposition of inhaled particles; the flow patterns vary inherently between patients. This paper provides an evaluation of the effects of six airflow patterns on the behaviour of inhaled particles, as determined by using numerical simulations. Methods Constant‐velocity and unsteady inhalation flows were employed. The unsteady inhalation flow was set as an inhalation curve with a peak inspiratory flow rate. Under a constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…We also found that some microparticles may travel and deposit in the sinus area, due to turbulent dispersion and secondary flow as described in rabbits (35). But in humans, the inhaled particles of 1 μm are effectively delivered distally (21), contrary to our results. In rodents, the maxilloturbinate region has been recognized as a very important and highly complex structure, accounting for over 50% airways resistance, bifurcating in several branches, and, in rabbits, acting as a filter for inhaled particles (35,36).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…We also found that some microparticles may travel and deposit in the sinus area, due to turbulent dispersion and secondary flow as described in rabbits (35). But in humans, the inhaled particles of 1 μm are effectively delivered distally (21), contrary to our results. In rodents, the maxilloturbinate region has been recognized as a very important and highly complex structure, accounting for over 50% airways resistance, bifurcating in several branches, and, in rabbits, acting as a filter for inhaled particles (35,36).…”
Section: Discussioncontrasting
confidence: 87%
“…Li and co-workers in 2007 demonstrated that deposition of micro-particle is due to impaction, secondary flow convection, and turbulent dispersion (46,47). For this reason, in humans particles tend to deposit mainly at stagnation points (oral cavity, pharynx, larynx, and trachea) and rarely reach the deep bronchial region (21). In this study, deposition tends to be higher in the muzzle and in the nasal turbinates region due to its complex structure and the deposition was lower in the oropharynx and tracheal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another trend of the human airway simulations is to use time-varied breath rates rather than steady breath rates. 7,17,18 Temporal scaling for application to transient airway modeling has not been investigated in the literature prior. Another challenge for the large-scale airway simulations would be the application of appropriate physics.…”
Section: Introductionmentioning
confidence: 99%
“…If not handled in a multiscale way, the upper coarse zones may waste numerous computational resources by using smaller timesteps. Another trend of the human airway simulations is to use time‐varied breath rates rather than steady breath rates 7,17,18 . Temporal scaling for application to transient airway modeling has not been investigated in the literature prior.…”
Section: Introductionmentioning
confidence: 99%